Going Viral : COVID-19 and the Accelerated Transformation of Jobs in Latin America and the Caribbean - Beylis, Guillermo (Washington, DC: World Bank, 2020)
The economic impact of COVID-19 is unprecedented in size and scope. It has quickly evolved from a health emergency into an employment crisis. It also has far-reaching implications for workers beyond the immediate employment effects, as it most likely has accelerated the transformation process of jobs that had already started in the region and the world. This book focuses on three important pre-pandemic trends observed in the region—namely, premature deindustrialization, servicification of the economy, and task automation—that were significantly changing the labor market landscape in the region and that have been accelerated by the crisis. While there is still uncertainty about the economic impacts of Covid-19, policymakers need to start planning for a rapidly evolving future that will come sooner than expected. A strong focus on productivity, technology development and adoption, and training in relevant skills will be key to adapting and taking advantage of the new opportunities in the post-pandemic world. Importantly, the accelerated transformation of jobs calls for a rethinking of labor regulations and social protection policies geared towards wage earners employed in the formal sector of the economy. The three trends identified in Going Viral, the effects of the pandemic itself, and the growing reliance on electronic platforms raise doubts that wage employment will increase substantially in the coming years. At the same time, earnings and transactions processed through electronic platforms are more visible to the authorities, bringing an opportunity to increase tax revenue and social security contributions. The flexible regulation of the emerging forms of work in a way that encourages employment, supports formalization, and expands the coverage of social protection to larger segments of the population will be of utmost importance for policymakers preparing for a new and changed world.